Legal aspects of articular cartilage tissue engineering experimentation: a review on Malaysian acts, regulations and guidelines - Radzi, Muhammad Aa'zamuddin Ahmad; Zawawi, Majdah; Munirah, Sha'ban; Azharuddin, Nur Syamimi Mohd; Noor Azmi, Azran Azhim; Hashi, Abdurezak Abdulahi (Faculty of Medicine and Health Sciences, 2020)
Presently, there is no specific federal legislation governing articular cartilage tissue engineering (ACTE) experimentation practices in Malaysia. However, there are related regulations and guidelines provided by government agencies to oversee and guide such practices. The rules and regulations provided in the documents have the essential aim of safeguarding public health through ensuring that non-clinical studies reach a certain quality, efficient and safe for human use. There are themes identified when scrutinising relevant documents which includes, the need for authorised personnel and the establishment of facilities in conducting such experiments, the aspect of cell-scaffold construct development, the use of human materials, the aspect of biosafety, animal care and use during the experiments, and considerations on the impact on the environment. The individual laboratory or facility shall adopt and adapt these standards as deemed appropriate by the ACTE researchers to ensure that non-clinical studies are conducted in a proper and ethical manner.